Electrical spectrum and network analyzers : a practical approach - Helfrick, Albert D. (Academic Press, 1991)
This book presents fundamentals and the latest techniques of electrical spectrum analysis. It focuses on instruments and techniques used on spectrum and network analysis, rather than theory. The book covers the use of spectrum analyzers, tracking generators, and network analyzers. Filled with practical examples, the book presents techniques that are widely used in signal processing and communications applications, yet are difficult to find in most literature. Key Features. Presents numerous practical examples, including actual spectrum analyzer circuits. Instruction on how to use spectrum analyzers, tracking generators, and network analyzers. End-of-chapter questions, which make the book suitable as a college-level text.